Cardiac remodeling in university athletes: non-contrast magnetic resonance imaging study - Liang, Hongqin; Kong, Li; Yang, Xi; Wang, Jian; Diao, Kaiyue (International Journal of Sports Medicine, 2025)
Early detection of exercise-induced cardiac anomalies is a key to clinical management for individuals engaged in vigorous exercise training. This study aimed to investigate cardiovascular adaptation in university students engaged in intensive exercises using cardiac magnetic resonance imaging. For this prospective, single-center study, 50 university students who finished a four-year intensively endurance training and 23 age- and gender- matched controls received cardiac magnetic resonance imaging. Exercised participants were further divided into symptomatic and asymptomatic groups. Left ventricular volumes and volumes indexed to the body surface were calculated. Global peak strains and systolic and diastolic peak strain rates were derived from cine images using a feature tracking technique. Analysis of variance analyses were performed. Fifty exercised participants (mean age: 21±1 y; 43 males, including 21 symptomatic and 29 asymptomatic cases) and 23 normal controls (mean age: 21±2 y, 20 males) were evaluated. Exercised participants exhibited a higher end-diastolic left ventricular volume (76.0±10.6 ml vs. 63.5±7.5 ml, p<0.001), a reduced left ventricular ejection fraction (59.9%±5.3 vs. 63.0%±3.2, p=0.002) and a reduced global longitudinal strain (−18.25±3.32 vs.−19.85±1.29, p=0.004) than the normal control participants. Symptomatic excised participants showed reduced peak strains compared to both asymptomatic participants and normal controls. Only a circumferential diastolic peak strain rate was reduced when compared between asymptomatic cases and controls. In conclusions, highly intensive exercises could result in elevated left ventricular volumes and reduced myocardial strains for young university students. Furthermore, reduced myocardial strains were found for those symptomatic cases which remain within non-pathological ranges.
Keywords: cardiac magnetic resonance; left ventricular remodeling; myocardial strain; strain rate; exercise Training